Emotional Regulation and Metacognitive Strategies in Psychology Students of a Private University from Arequipa, Peru - Arias Gallegos, Walter L. (2026)
Objective. Although emotions play an important role in metacognition, little research has been done on how metacognitive strategies are related to emotional regulation. Hence, this paper aims to determine the predictive power of emotional regulation on metacognition in university students. Method. 247 university students from a private university in Arequipa were evaluated for this purpose. The Cognitive and Emotional Regulation Questionnaire (CERQ-18) was used, in addition to the Metacognitive Strategies Inventory. Both instruments were previously validated in Peru. Results. It was found that blaming others negatively influences metacognition (β = -0.978; p = .004), while focusing on plans positively influences it (β = 2.69; p < .001). To conclude, emotional regulation is a variable that impacts the metacognition of university students.